THE SOCIAL ASPECTS OF REHABILITATION OF DRUG-ADDICTED ADOLESCENTS - Shimanovskaya ,; Sarychev,; Kozlovskaya, (Revista Inclusiones, 2020)
The risk of drug addiction presents a relatively new problem to the Russian reality, which determines the lack of an effective method for its management, as well as objectively full awareness of the seriousness of the threat. The article presents the analysis of specific characteristics of working with people suffering from drug addiction. The methods and technologies for social work with people with drug addiction are researched. The primary difficulties in social workers’ professional activity and the obstacles to effective work with drug addicts are identified. The specific features of social rehabilitation of drug addicts and the requirements for social workers’ competence are formulated.